(untitled) (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: To design and develop a gastroretentive herbal formulation of Coccinia grandis for the treatment of Helicobacter pylori infection. Material and Methods: C. grandis extract was obtained by soxhlation process with ethanol as the menstrum. The herbal gastroretentive tablets containing 200 mg of C. grandis ethanolic extract were prepared by direct compression method using effervescent technique. HPMC K4M, HPMC K100M, Carbopol and guar gum were used as retarding polymers at various concentrations. Sodium bicarbonate was used at 20%w/w as gas generating agent and Avicel at 35%w/w as diluent. FTIR and DSC methods were employed to investigate the drug-excipient interactions. The formulated tablets were evaluated for various quality control parameters. Results and Discussion: The FTIR and DSC study revealed that there was no interaction between the extract and the excipients. All the formulated tablets were within the quality control limits. The kinetic studies specified that the release of extract from the gastroretentive tablets was by erosion-controlled diffusion mechanism. Conclusion: The formulation having the combination of gum with HPMC K15M exhibited minimum floating lag time and good release pattern which followed first-order kinetics.